LANGUAGE ERROR FORM ANALYSIS IN THE ESSAY OF CLASS XI STUDENTS OF SMA NEGERI 1 MAKASSAR - Abriani, Wahyu Dwi; Darwis, Muhammad; Kaharuddin, Kaharuddin (International Journal of Social Science, 2022)
This research aims to analyze the form of language errors in the essays of class XI students of SMA Negeri 1 Makassar. This type of research method, that is, a descriptive research method. The technology of data analysis used in this study is prescriptive. The type of data that will be used in this study is in the form of student essay text. The results showed that there were four forms of language errors, namely in the form of addition, subtraction, word choice, and arrangement.